A Bifunctional Electrolyte Additive Features Preferential Coordination with Iodine toward Ultralong‐Life Zinc–Iodine Batteries - Wang, Feifei; Liang, Wenbin; Liu, Xinyi; Yin, Tianyu; Chen, Zihui; Yan, Zhijie; Li, Fangbing; Liu, Wei; Lu, Jiong; Yang, Chunpeng; Yang, Quan‐Hong (Advanced energy materials, 2024)
Aqueous zinc–iodine (Zn‐I2) battery is one of the most promising candidates for large‐scale energy storage due to its cost‐effectiveness, environmental friendliness, and recyclability. Its practical application is hindered by challenges including polyiodide “shuttle effect” in the cathode and anode corrosion. In this study, a zinc pyrrolidone carboxylate bifunctional additive is introduced to simultaneously tackle the issues of the polyiodide and Zn anode. It is revealed that the pyrrolidone carboxylate anions decrease the polyiodide concentration by preferential coordination between the pyrrolidone carboxylate anions and I2 based on the Lewis acid‐base effect, suppressing the shuttle effect and therefore improving the conversion kinetics for the iodine redox process. Meanwhile, the pyrrolidone carboxylate anions adsorbed on the Zn anode inhibit Zn corrosion and promote non‐dendritic Zn plating, contributing to impressive Coulombic efficiency and long‐term cycling stability. As a result, the Zn‐I2 full battery with the bifunctional zinc pyrrolidone carboxylate additive realizes a high specific capacity of 211 mAh g−1 (≈100% iodine utilization rate), and an ultralong cycling life of >30 000 cycles with 87% capacity retention. These findings highlight the significant potential of zinc pyrrolidone carboxylate as a transformative additive for aqueous Zn‐I2 batteries, marking a critical advancement in the field of energy storage technologies. The study uses a zinc pyrrolidone carboxylate additive to reduce polyiodide concentration by preferential coordination with I2, following the Lewis acid–base effect. This suppresses the shuttle effect and improves conversion kinetics of iodine species. Furthermore, pyrrolidone carboxylate anions pre‐adsorb zinc anodes, impeding corrosion and promoting non‐dendritic zinc plating/stripping. Consequently, the zinc‐iodine battery demonstrates an ultralong cycling lifespan (>30 000 cycles).